Microfluidics-Based Nanobiosensors for Healthcare Monitoring - Kumari, Monika; Gupta, Verruchi; Kumar, Natish; Arun, Ravi Kumar (Molecular biotechnology, 2024)
Efficient healthcare management demands prompt decision-making based on fast diagnostics tools, astute data analysis, and informatics analysis. The rapid detection of analytes at the point of care is ensured using microfluidics in synergy with nanotechnology and biotechnology. The nanobiosensors use nanotechnology for testing, rapid disease diagnosis, monitoring, and management. In essence, nanobiosensors detect biomolecules through bioreceptors by modulating the physicochemical signals generating an optical and electrical signal as an outcome of the binding of a biomolecule with the help of a transducer. The nanobiosensors are sensitive and selective and play a significant role in the early identification of diseases. This article reviews the detection method used with the microfluidics platform for nanobiosensors and illustrates the benefits of combining microfluidics and nanobiosensing techniques by various examples. The fundamental aspects, and their application are discussed to illustrate the advancement in the development of microfluidics-based nanobiosensors and the current trends of these nano-sized sensors for point-of-care diagnosis of various diseases and their function in healthcare monitoring.